Fiord to Deep Sea Sediment Transfers along the Northeastern Canadian Continental Margin: Models and Data - Andrews, John (Géographie physique et Quaternaire, 1990)
ABSTRACTIn Alaskan fiords, sedimentation rates are high; during a glacial advance fiord-basin sediments are transported to the ice front to form a shoal which reduces the calving rate. Thus, during successive glacial cycles, sediment is initially stored and then removed from fiord basins. In the fiords of eastern Baffin Island sedimentation rates are, and were, much lower (< 1000 Kg/m2 ka). and fiord-basin fills may span several glacial cycles. This hypothesis is in keeping with the relatively low sedimentation rates on the adjacent shelf (50 to 500 kg/m2 ka) and deep-sea plain (< = 50 kg/m2 ka). The advance of outlet glaciers through these arctic fiords may be explained by the in situ growth of a floating ice-shelf, grounded at the mouth of the fiord. The extent of late Foxe Glaciation in McBeth and ltirbilung fiords can be delimited by raised marine deltas (50-85 m asl) with 14C dates on in situ shells and whalebone of >54 ka. Holocene raised beaches are lower and date <10 ka. These data, plus the absence of tills in raised marine sections along the outer coast, make it difficult to extend grounded ice onto the shelf during the 18 ka global maximum. Piston cores from Tingin. ltirbilung and McBeth fiords vary between 4 and 11 m in length, but only sample a proportion of the total basin-fills.